A study of CP violation in B± → DK± and B± → Dπ± decays with D → K0SK±π[minus-plus sign] final states - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; et al. (Physics letters, 2014)
A first study of CP violation in the decay modes B±→[KS0K±π∓]Dh± and B±→[KS0K∓π±]Dh±, where h labels a K or π meson and D labels a D0 or D‾0 meson, is performed. The analysis uses the LHCb data set collected in pp collisions, corresponding to an integrated luminosity of 3 fb−1. The analysis is sensitive to the CP-violating CKM phase γ through seven observables: one charge asymmetry in each of the four modes and three ratios of the charge-integrated yields. The results are consistent with measurements of γ using other decay modes.
Im Titel sind "±", "minus-plus sign" und "0" hochgestellt und "S" in K0SK±π∓ tiefgestellt
Gesehen am 24.07.2020